1999
DOI: 10.1093/jn/129.8.1579
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acids Alter Milk Fatty Acid Composition and Inhibit Milk Fat Secretion in Dairy Cows

Abstract: Conjugated linoleic acids (CLA) have positive health effects in experimental models. Our objective was to determine the effect of CLA supplementation on milk of dairy cows. A commercial source of CLA was infused abomasally to by-pass rumen fermentation. The supplement contained 61.2% CLA; the major CLA isomers were cis/trans 8,10, cis/trans 9,11, cis/trans 10,12 and cis/trans 11,13. Four Holstein cows were used in a 4 x 4 Latin square design. Treatments were 5-d infusions of 0, 50, 100 and 150 g/d of CLA suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
280
5
19

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(340 citation statements)
references
References 19 publications
36
280
5
19
Order By: Relevance
“…Ip et al, 2002;Kelley et al, 2007) and reduced adiposity (reviewed by Pariza, 2004), although only a mixed preparation including both cis-9, trans-11 and trans-10, cis 12 CLA was available in the original experiments. Similarly, this mixed CLA preparation also reduced milk fat yield in dairy cows (Loor and Herbein, 1998;Chouinard et al, 1999a and1999b). Subsequently, the ability to prepare relatively pure CLA isomers allowed the seminal demonstration by Baumgard et al (2000) that trans-10, cis-12 CLA markedly reduced milk fat synthesis, whereas cis-9, trans-11 CLA had no effect ( Figure 2).…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 92%
“…Ip et al, 2002;Kelley et al, 2007) and reduced adiposity (reviewed by Pariza, 2004), although only a mixed preparation including both cis-9, trans-11 and trans-10, cis 12 CLA was available in the original experiments. Similarly, this mixed CLA preparation also reduced milk fat yield in dairy cows (Loor and Herbein, 1998;Chouinard et al, 1999a and1999b). Subsequently, the ability to prepare relatively pure CLA isomers allowed the seminal demonstration by Baumgard et al (2000) that trans-10, cis-12 CLA markedly reduced milk fat synthesis, whereas cis-9, trans-11 CLA had no effect ( Figure 2).…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 92%
“…The total concentrations of MUFAs and CLA should increase in fat if SCD activity rises, improving in this way the nutritional quality of milk. Some studies estimated SCD activity by specific FA indices, defined as ratios of FAs dependent on this enzymatic activity: product/substrate (e.g., Lock and Garnsworthy 2003), substrate/product (e.g., Chouinard et al 1999) or product/(substrate + product) (e.g., Kelsey et al 2003). Kelsey et al (2003) observed that Holstein cows showed higher FA indices compared to Brown-Swiss cows, except for CLA index.…”
Section: Breed Differencesmentioning
confidence: 99%
“…Biohydrogenation of polyunsaturated fatty acids (PUFAs) generates isomers of conjugated linoleic acid (CLA) that depress milk fat synthesis of short and medium chain fatty acids (FAs) in the mammary gland, and causes a reduction in milk fat content and yield (Chouinard et al, 1999;Baumgard et al, 2000). Abomasal infusion of pure isomers of CLA by Baumgard et al (2000) identified the trans-10, cis-12 CLA as the main responsible isomer for the milk fat depression (MFD).…”
Section: Introductionmentioning
confidence: 99%